A rare cause of acute abdomen: acute cholecystitis secondary to polyarteritis nodosa - Zeki DÖŞEYEN; Aydın İNAN and Sancar BAYAR and Cihan BUMİN and Mahmut KESENCİ and Özden TOLUNAY (Turkish Journal of Gastroenterology, 2019)
-